ANALYSIS OF DAY-OLD CHICK DISTRIBUTION ROUTES WITH SAVING MATRIX METHOD AND DETERMINATION OF VEHICLE OPERATIONAL COSTS AT PT. BERDIKARI (PERSERO) - Utama, Muhamad Dipa Adri Juan; Wicaksono, Bagas; Wirabuan, Rangga; Maulana, Diva; Kartanegara, Guruh; Margana, Riki Ridwan (CENTRAL ASIA AND THE CAUCASUS, 2022)
PT Berdikari (Persero) has started to produce DOC (Day-Old Chick) which is distributed to smallholder breeders and is spread across Java and other regions throughout Indonesia. One of the problems with CVRP in the distribution process is that PT Berdikari (Persero) must use 4 car body trucks in the process of distributing DOC on each route to 12 cities/districts so that the DOC distribution process is deemed not optimal in terms of distance, vehicle fleet capacity, and transportation costs. The purpose of this study is to provide a more effective delivery route for DOC products and is also expected to obtain a minimum cost. Determining the solution to this CVRP problem using the saving matrix method, this method allows route optimization by considering the capacity of the vehicle fleet. The results of the discussion using the saving matrix method showed a decrease in distribution routes from 12 cities/districts to 4 routes with a travel time of 21.84 hours, the improvement process accelerated the delivery of goods from 3 days to 1 day. The total distribution distance of 12 cities/districts is 1069.4 km. The total vehicle operating costs incurred by PT Berdikari (Persero) in the existing condition is Rp.9.191.549,91 and after using the saving matrix method, it is Rp.3.733.549,84. Total savings of vehicle operating costs are Rp. 5.458.045,07 or 59,38%.